Recent advances in peptide signaling during Arabidopsis root development. (17th February 2021) - Jeon, Byeong Wook; Kim, Min-Jung; Pandey, Shashank K; Oh, Eunkyoo; Seo, Pil Joon; Kim, Jungmook
Abstract: Roots provide the plant with water and nutrients and anchor it in a substrate. Root development is controlled by plant hormones and various sets of transcription factors. Recently, various small peptides and their cognate receptors have been identified as controlling root development. Small peptides bind to membrane-localized receptor-like kinases, inducing their dimerization with co-receptor proteins for signaling activation and giving rise to cellular signaling outputs. Small peptides function as local and long-distance signaling molecules involved in cell-to-cell communication networks, coordinating root development. In this review, we survey recent advances in the peptide ligand-mediated signaling pathways involved in the control of root development in Arabidopsis. We describe the interconnection between peptide signaling and conventional phytohormone signaling. Additionally, we discuss the diversity of identified peptide–receptor interactions during plant root development. Abstract : This review describes recent findings on the peptide signaling that controls various aspects of Arabidopsis root development, and illustrates the interconnection of peptide signaling with conventional phytohormone signaling.